Low Self-Control, Substance-Using Peers and Intimate Partners, Pro-Drug Use Definitions, and Inhalant Use Among Convicted Offenders in South Korea - Choi, Jaeyong (Journal of drug issues, 2021)
Hirschi has repeatedly argued that the relationship between social learning variables and crime is a product of “self-selection” driven by low self-control (LSC). Akers’ has suggested that social learning mechanisms, such as affiliations with deviant individuals and acceptance of criminal definitions, can mediate the effects of LSC on crime. Interestingly, there has been little comparative work done to explore this mediation hypothesis in the realm of substance use for offender populations outside of the United States. This study helps fill these gaps in the literature by exploring the potential mediation effects of social learning variables on the relationship between LSC and inhalant use among a sample of 739 male offenders in South Korea. Our results provide strong support for the mediation hypothesis that LSC indirectly influences self-reported inhalant use through social learning mechanisms.